El stop motion como herramienta de lectura crítica del uso de la imagen de los niños en anuncios publicitarios en televisión. (Caso: productos de aseo, cuidado personal y multivitamínicos) - Almeida Mesías, Mayra Alejandra (2014)
Nowadays, the information and communication technology occupy an important place in the life of individuals and societies. Its evolution and prominence have made possible the birth of the information societies, within which they are framed mass communication and cultural industries. One of the most popular products in the culture industry is the television, a medium where information abounds. This information includes advertisements which are an example of mass communication and are created as an attempt to promote consumption and to reach specific groups such as children and girls.